Full Day School dalam Pengembangan Bakat dan Minat Siswa: Full Day School in the Development of Students' Talents and Interests - Imroatus Solihah (Fenomena, 2016)
Education is closely related to all aspects of human development, including physical, intellectual, emotional, social, and spiritual growth. This development helps humans achieve perfection, improve their lives, and transform natural existence into a civilized and moral one. Students are raw components who need guidance through various instructional activities at school to become the expected graduates. Each learner possesses unique potential, as everyone is born with distinct talents and innate traits, such as the inclination toward monotheism or other inherent abilities. The study results indicate that the talent and interest development program is implemented through extracurricular activities, consisting of compulsory and additional programs. The compulsory program is scouting, while the additional programs include the Science Club, Mathematics Club, English Club, Arabic Club, Exemplary Students, Rohis (Quran recitation and call to prayer), Rohis (Quranic recitation), Rohis (calligraphy), Rohis (Quran memorization), Speech, Presenter, Young Preacher, MC, Choir and Nasyid, Hadroh, Poetry and Short Story Writing, Football or Futsal, Badminton, ICT, BCM, Taekwondo, and Martial Arts. The program is supported by semester plans, annual plans, and extracurricular journals. Evaluation is conducted at the end of the program to ensure the objectives are met. Pendidikan berkaitan erat dengan segala hal yang terkait dengan perkembangan manusia, seperti perkembangan fisik, pikiran, perasaan, kemauan, sosial, hingga perkembangan iman. Perkembangan ini menjadikan manusia lebih sempurna, meningkatkan kehidupan mereka, dan mengubah kehidupan alamiah menjadi kehidupan yang beradab dan bermoral. Siswa merupakan komponen mentah yang perlu dibimbing melalui berbagai kegiatan pembelajaran di sekolah agar menjadi lulusan yang diharapkan. Setiap peserta didik memiliki potensi yang berbeda-beda karena setiap orang dilahirkan dengan berbagai bakat yang unik dan membawa fitrahnya masing-masing, seperti dorongan untuk bertauhid atau potensi bawaan lainnya. Hasil penelitian menunjukkan bahwa program pengembangan bakat dan minat siswa diimplementasikan melalui kegiatan ekstrakurikuler, yaitu program wajib dan program tambahan. Program wajib adalah pramuka, sedangkan program tambahan meliputi Klub Sains, Klub Matematika, Klub Bahasa Inggris, Klub Bahasa Arab, Siswa Teladan, Rohis (Tartil dan Adzan), Rohis (Tilawah), Rohis (Kaligrafi), Rohis (Tahfidz), Pidato, Presenter, Da'i Cilik, MC, Paduan Suara dan Nasyid, Hadroh, Puisi dan Menulis Cerpen, Sepak Bola atau Futsal, Bulu Tangkis, TIK, BCM, Taekwondo, dan Pencak Silat. Pelaksanaan program ini didukung oleh perencanaan semester, rencana tahunan, dan jurnal ekstrakurikuler. Evaluasi dilakukan pada akhir program untuk memastikan tujuan tercapai.